2014
DOI: 10.1302/0301-620x.96b6.33201
|View full text |Cite
|
Sign up to set email alerts
|

Graft-bending angle and femoral tunnel length after single-bundle anterior cruciate ligament reconstruction

Abstract: We used immediate post-operative in vivo three-dimensional computed tomography to compare graft bending angles and femoral tunnel lengths in 155 patients who had undergone single-bundle reconstruction of the anterior cruciate ligament using the transtibial (n = 37), anteromedial portal (n = 72) and outside-in (n = 46) techniques. The bending angles in the sagittal and axial planes were significantly greater but the coronal-bending angle was significantly less in the transtibial group than in the anteromedial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 31 publications
4
33
0
Order By: Relevance
“…39 The femoral tunnel axis was found to be lowest after use of the OI technique and more than half of the value reported by Shin et al 31 Robert et al 28 used the anatomic longitudinal axis of the femur to determine the angle of the femoral tunnel axis but also found statistically significant differences between all groups in a cadaveric setting, indicating the most oblique femoral graft entry with OI drilling. Even though gentler graft bending angles were found with AMP technique, 15 the OI retrograde drilling offers substantial variability in adjusting the femoral drill guide.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…39 The femoral tunnel axis was found to be lowest after use of the OI technique and more than half of the value reported by Shin et al 31 Robert et al 28 used the anatomic longitudinal axis of the femur to determine the angle of the femoral tunnel axis but also found statistically significant differences between all groups in a cadaveric setting, indicating the most oblique femoral graft entry with OI drilling. Even though gentler graft bending angles were found with AMP technique, 15 the OI retrograde drilling offers substantial variability in adjusting the femoral drill guide.…”
Section: Discussionmentioning
confidence: 87%
“…In contrast, assessments of AMP techniques have revealed diminished femoral tunnel length and possible effect on graft fixation when compared with the TT 33 and OI techniques. 22 Only a few studies 10,30,31 have reported a comprehensive characterization of TT, AMP, and OI femoral and tibial tunnels in vivo and have studied whether one of the techniques might be superior with respect to accurate anatomic replacement in the center of the native attachment site. In addition, the usefulness of axial CT scans as reported in the literature is restricted by a limited applicability during surgery.…”
mentioning
confidence: 99%
“…At an alpha level of 0.05 and a power of 0.8, 17 patients for each group would be required to detect a mean difference of 8 degrees for the femoral graft bending angle as calculated using power and sample size calculations version 3.0 based on previous reports [12,23].…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have analyzed the femoral graft bending angle between femoral tunnel axis and graft at the femoral tunnel aperture in ACL reconstruction [12,16,18,23,26,27]. However, the relationship between femoral tunnel location and femoral graft bending angle has been little investigated.…”
Section: Introductionmentioning
confidence: 99%
“…This is based on the fact that, unlike the tibial tunnel, which will be in line with the reconstructed ACL, the femoral tunnel is oriented at a divergent angle to the reconstructed ACL when the femoral tunnel is placed anatomically through a far medial portal. 16,17 This divergence between the femoral tunnel and the reconstructed ACL by itself improves the pull-out strength of the femoral bone plug.…”
Section: Discussionmentioning
confidence: 99%